A CASE STUDY ON TOTAL BUILDING PERFORMANCE EVALUATION OF AN INTELLIGENT OFFICE BUILDING IN SINGAPORE - Po Seng Kian; Henry Feriadi; Wiliana Sulistio; Kong Chee Seng (Civil Engineering Dimension, 2001)
The importance of understanding the performance of a building in a holistic sense is undeniable. This paper presents a method of total building performance evaluation, which has been widely used in many developed countries including Singapore. An office building with apartment and commercial retails called “intelligent building” is selected for building diagnosis. The occupant surveys and physical walkthroughs are carried out as subjective evaluations, while some objective measurements of indoor air quality and visual quality are also introduced in this study. The results indicate that generally, the occupants are satisfied with the quality of the building despite some insignificant indoor air quality and visual symptoms due to low temperature and glare problem in the office.